DIVERSITY AND DISTRIBUTION OF RAPTORS AT GUNUNG HALIMUN NATIONAL PARK WITH PARTICULAR REFERENCE TO JAVAN HAWK- EAGLE - Prawiradilaga, Dewi M (Research Center for Biology-Indonesian Institute of Sciences, 2001)
Although the role of raptors as the top predators in the food chain is important to maintain the balance of an ecosystem, in Indonesia they have rarely been studied.This paper presents the most comprehensive study on the diversity and distribution of raptors with emphasize on Javan Hawk-eagle at Gunung Halimun National Park, the largest remnant forest in Java.The raptor study has been done by field surveys,long watches at selected observation sites and collecting information from previous reports.The results showed that there are 17 raptor species recorded in the area.Furthermore, the Crested Serpent eagle (Spilornis cheelo),Black Eagle (Ictinaetus malayensis), and Javan Hawk-eagle Spizaetus bartelsi) were recorded in many locations.However,the Black-winged Kite Elanus caeruleus), Brahminy Kite (Haliastur Indus), Lesser Fish-eagle (Ichthyophaga ichthyaetus),Japanese Sparrowhawk (Accipiter gularis) and the White-bellied sea-eagle (Haliaeetus leucogaster) were observed only in one location. In addition, the Javan Hawk-eagle was recorded at 14 locations namely G. Halimun Utara, G. Buligir Putih, Pasir Cangkuang, G. Malang, West Halimun, G. Bodas, G. Tumpeng, G. Citimur, G. Bengreng, G. Batu, Cadas Mahpar, G. Kempul, G. Kendeng and G. Botol.The number of observed Javan Hawk-eagle individuals at G. Botol was higher than in other locations.",